Small Prose Constants by F. Sologub - О. I. Osipova (Научный диалог)
The question of constants in the short prose of F. Sologub is considered. Special attention is paid to the iconic cycle of stories in the work of the author. The results of the analysis of motives, chronotope, recurring elements of the plot and the system of characters in the cycles “The Sting of Death” and “Unkind Lady” are presented. It is shown with the help of comparative and intertextual methods that in the stories of the cycles the constant binary opposition of a meaningless, cruel life and a consoling death is embodied, the hero’s dreams of death determine the meaninglessness of being. It has been proved that time and partly space in the stories of the cycles are binary organized, but this is not the duality of this and other worlds: the hero does not go beyond the boundaries of this world, but the time and space of this world change under the influence of the altered consciousness of the hero. The author dwells on the analysis of motivational complexes that also represent oppositions, which allows us to conclude that there are constant signs of Sologub’s artistic world. The novelty of the research lies in the fact that modern comprehension of classical works using a new technique made it possible to see the internal complex interconnection of texts, to find explicit and implicit signs of interaction between cycles.